On "The Methodology of Positive Economics" - Rotwein, Eugene (Quarterly Journal of Economics, 1959)
I. Introduction, 554. — II. Friedman's main thesis evaluated, 556. — III. Other aspects of Friedman's argument considered, 564. — IV. Conclusion, 570.